2015
DOI: 10.1016/j.jana.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

“I Should Know Better”: The Roles of Relationships, Spirituality, Disclosure, Stigma, and Shame for Older Women Living With HIV Seeking Support in the South

Abstract: The population of older people living with HIV in the United States is growing. Little is known about specific challenges older HIV-infected women face in coping with the disease and its attendant stressors. To understand these issues for older women, we conducted semi-structured in-depth interviews with 15 women (13 African American, 2 Caucasian) 50 years of age and older (range 50–79) in HIV care in the Southeastern United States, and coded transcripts for salient themes. Many women felt isolated and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 34 publications
10
71
1
1
Order By: Relevance
“…Stigmatization can also increase medication adherence issues (Li, Murray, K., Suwanteerangkul, & Wiwatanadate, 2014), and can increase sexual risk behaviour among people living with HIV (Teti, Bowleg, & Lloyd, 2010; Wingood et al, 2007). In our findings, HIV is described as something that complicates, which is in line with the findings of previous research (Cuca & Rose, 2016; Grodensky et al, 2015; Ho, Goh, & L., 2017). …”
Section: Discussionsupporting
confidence: 93%
“…Stigmatization can also increase medication adherence issues (Li, Murray, K., Suwanteerangkul, & Wiwatanadate, 2014), and can increase sexual risk behaviour among people living with HIV (Teti, Bowleg, & Lloyd, 2010; Wingood et al, 2007). In our findings, HIV is described as something that complicates, which is in line with the findings of previous research (Cuca & Rose, 2016; Grodensky et al, 2015; Ho, Goh, & L., 2017). …”
Section: Discussionsupporting
confidence: 93%
“…Grodensky et al [25] interviewed 15 OWLH to explore their experiences living with HIV and found that only four participants reported SA. Those participants without sexual partners either had ended past relationships by choice or were abandoned, or their partner died.…”
Section: Sexual Healthmentioning
confidence: 99%
“…Grodensky et al [25] described family (especially daughters) and platonic relationships as the main sources of social support. Spirituality and private relationship with God also emerged as an important coping strategy, even though women did not rely much on church for social support and rarely disclosed their HIV status within their congregations.…”
Section: Psychosocial Issues and Protective Factorsmentioning
confidence: 99%
“…Whatever the source, stigma affects disclosure patterns, health outcomes, and quality of life for those living with HIV [43,[60][61][62]. Social support has been identified as a facilitator of self-management of HIV and significantly associated with positive coping for women living with HIV [16,63]. African American women who encounter and/or anticipate stigma related to HIV, may infer that engaging in HIV self-management might disclose their serostatus directly or indirectly-thus, jeopardizing their actual or potential social support networks.…”
Section: Engagement In Hiv Care Treatment and Self-managementmentioning
confidence: 99%